UMP Foundation donates school equipment for staffs children - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 13 March 2023 - A total of 100 children of Universiti Malaysia Pahang (UMP) staff received donations of school uniforms in conjunction with the Back To School program organized by the UMP Foundation and the Registrar's Department which was held at both UMP Pekan and Gambang Campus.